2002
DOI: 10.1080/10473289.2002.10470788
|View full text |Cite
|
Sign up to set email alerts
|

Respirable Particulate Matter at an Urban and Nearby Industrial Location: Concentrations and Variability and Synoptic Weather Conditions during High Pollution Episodes

Abstract: Continuous data of the concentration measurements of respirable suspended particulates (PM 10 , particles with aerodynamic diameter smaller than or equal to 10 µm) were analyzed. These measurements were carried out at an urban and nearby industrial location in northern Greece for the 5-year period 1996-2000. The time series concentration trend was examined, the seasonal and diurnal variations were identified, and the lognormality of the daily mean concentration data sets was tested. Over the 5-year data-gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 13 publications
2
40
0
1
Order By: Relevance
“…Using a synoptic climatological approach, other studies 4,5 have assessed the impacts of weather on ambient levels of PM at various worldwide locations. Additionally, ambient measurements of particle component and gaseous co-pollutant concentrations have been used to study the processes leading to the secondary formation of these particle components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a synoptic climatological approach, other studies 4,5 have assessed the impacts of weather on ambient levels of PM at various worldwide locations. Additionally, ambient measurements of particle component and gaseous co-pollutant concentrations have been used to study the processes leading to the secondary formation of these particle components.…”
Section: Discussionmentioning
confidence: 99%
“…SO 2 is a precursor to the secondary formation of SO 4 2Ϫ aerosol, and NO x is a precursor to the secondary formation of NO 3 Ϫ aerosol. Although statistically significant positive associations were observed between adjusted values of these secondary aerosol species and their gaseous precursors, the associations were relatively weak, especially for NO, NO 2 , and NO 3 Ϫ .…”
Section: Episodes Of Elevated Pm 25 Concentrationmentioning
confidence: 99%
“…For instance, Hansen et al 10 used hourly PM 2.5 and gaseous co-pollutant data to identify sources likely contributing to various PM 2.5 pollution episodes in the southeastern United States. Triantafyllou et al 11 used diurnal profiles to draw inferences about the influence of meteorological conditions and emission sources on hourly PM 10 concentrations in northern Greece, and Strohm et al 12 used hourly data to pinpoint the behavior of PM 2.5 concentrations in several midwestern U.S. cities in response to changes in weather conditions during a PM 2.5 episode. Other studies [13][14][15][16][17] have used time-resolved measurements of particular aerosol components to study the chemistry and origins of PM.…”
Section: Introductionmentioning
confidence: 99%
“…A typical example is the city of Kozani in Greece. It has a population of 70,000 inhabitants and recent studies have revealed the nature of the air pollution problem in the city (Triantafyllou et al, 2002). This is due to the fast economic growth in the last decades that resulted in an increase of the sources of pollution in the city of Kozani.…”
Section: Introductionmentioning
confidence: 99%